Integrative Longitudinal Analysis of Metabolic Phenotype and Microbiota Changes During the Development of Obesity - Higgins, Keah V.; Woodie, Lauren N.; Hallowell, Haley; Greene, Michael W.; Schwartz, Elizabeth Hiltbold (Frontiers in Cellular and Infection Microbiology, 2021)
Obesity has increased at an alarming rate over the past two decades in the United States. In addition to increased body mass, obesity is often accompanied by comorbidities such as Type II Diabetes Mellitus and metabolic dysfunction-associated fatty liver disease, with serious impacts on public health. Our understanding of the role the intestinal microbiota in obesity has rapidly advanced in recent years, especially with respect to the bacterial constituents. However, we know little of when changes in these microbial populations occur as obesity develops. Further, we know little about how other domains of the microbiota, namely bacteriophage populations, are affected during the progression of obesity. Our goal in this study was to monitor changes in the intestinal microbiome and metabolic phenotype following western diet feeding. We accomplished this by collecting metabolic data and fecal samples for shotgun metagenomic sequencing in a mouse model of diet-induced obesity. We found that after two weeks of consuming a western diet (WD), the animals weighed significantly more and were less metabolically stable than their chow fed counterparts. The western diet induced rapid changes in the intestinal microbiome with the most pronounced dissimilarity at 12 weeks. Our study highlights the dynamic nature of microbiota composition following WD feeding and puts these events in the context of the metabolic status of the mammalian host.